The dynamics of managing diversity and inclusion a critical approach - Kirton, Gill; Greene, Anne Marie (New York, NY Routledge, 2022)
"The Dynamics of Managing Diversity and Inclusion was one of the first books to respond to growing academic coverage of the topic of diversity management at degree level. This fifth edition has been fully updated to reflect new working practices, labour market data, organisational policies and developments in equality and diversity law, as well as including new case studies and analysis of current and emerging areas of debate in the UK and across Europe. Diversity management is a term that covers not only policy and practice on race, disability and sex discrimination, but also broader issues including other identity and cultural differences. The Dynamics of Managing Diversity and Inclusion, fifth edition, provides future HR professionals and business/organisational managers of the future with the legal information and research findings needed to enable them to participate in the development and implementation of meaningful diversity and inclusion policies in their organizations. This new edition offers: Inclusion of topical issues such as female and minority representation on executive boards, religious diversity, gender identity, Black Lives Matter and #MeToo movements; Multiple analytical perspectives, such as socio-legal and feminist approaches, to provide rich insights into the subject matter; Practical case studies and exercises to illustrate the real-life issues in a local, international and organizational context. The book deals with the subject of diversity management in a rigorous and structured manner, beginning each chapter with aims and objectives, providing key learning points and review and discussion questions at regular junctures, and ending with concluding thoughts and observations, making this book the perfect support resource for those teaching or studying in the field of equality, diversity and inclusion"--
Revised edition of the authors' The dynamics of managing diversity, 2016.
Includes bibliographical references and index.
Keywords: Diversity in the workplace; Diversity in the workplace -- Great Britain